Аномальные частоты в полубесконечном цилиндрическом сосуде с жидкостью при динамическом возбуждении сферическим излучателем - Кубенко, В.Д.; Янчевский, И.В. (Прикладная механика, 2020)
В данной работе рассматривается акустическая система, принятая к рассмотрению в публикации [22], однако предполагается, что среда испытывает динамическое возбуждение за счет излучаемого сферическим телом акустического давления. Целью работы является получение частотных зависимостей для давления и скорости при различных соотношениях геометрических параметров системы с целью выявления возможных аномальных частот, обусловленных волновым взаимодействием сферического тела с торцом сосуда. Розглядається заповнена ідеальною стисливою рідиною напівнескінченна кругова циліндрична порожнина, що містить розташоване поблизу її торця сферичне тіло. Поверхня тіла випромінює періодичний тиск із заданою частотою і амплітудою. Розв'язується задача визначення гідродинамічних характеристик системи залежно від частоти збудження і геометричних параметрів. Застосовується метод розділення змінних, трансляційні теореми додавання для сферичних хвильових функцій і співвідношення, що представляють сферичні хвильові функції через циліндричні і навпаки. Такий підхід дозволяє задовольнити усім граничним умовам і отримати точний розв'язок граничної задачі. Обчислення зведені до розв'язання нескінченної системи алгебраїчних рівнянь відносно якої стверджується, що її розв'язок методом зрізання сходиться. Визначення полів тиску і швидкості показало, що дана система має низку значень частоти збудження, при яких акустичні характеристики перевищують амплітуду збудження на декілька порядків. Ці аномальні частоти відрізняються від частот, властивих нескінченній циліндричній порожнині зі сферичним тілом. При цьому навіть у випадку, коли радіус сферичного випромінювача малий і аномальні явища в нескінченній посудині слабо виражені, в напівнескінченній порожнині вони можуть проявитися суттєво. A semi-infinite circular cylindrical cavity filled with an ideal compressible liquid which contains a spherical body located near to its end is considered. The body surface radiates the periodic pressure with the given frequency and amplitude. The problem of determining the hydrodynamic characteristics of the system depending on the frequency of excitation and geometrical parameters is solved. The method of separation of variables, the translational addition theorems for the spherical wave functions, and the relations representing the spherical wave functions through the cylindrical ones and inverse are applied. This approach allows to satisfy all boundary conditions and to obtain the exact solution of boundary problem. The calculations are reduced to solving the infinite system of algebraic equations. Further, it is asserted that its solution obtained by the truncation method converges. Determination of the pressure fields and velocities is displayed that the considered system has the series of frequencies of excitation at which the acoustic performances can exceed several orders the amplitude of excitation. These anomalous frequencies differ from the frequencies inherent for an infinite cylindrical cavity with a spherical body. Thus, even in a case when the radius of spherical emitter is small, and therefore the anomalous phenomena in an infinite vessel are poorly expressed, in a semi-infinite vessel they can appear essentially.